Reliability-centric maintenance applied to an ROV system - Pereira , Paulo Apicelo de Souza; Amaral , Mateus Carvalho; Ribeiro , Lucas Cardoso Ambrósio (Seven Editora, 2023)
The ROV – Remotely Operated Vehicle is one of the most used subsea equipment in the world oil and gas industry, it is to maintain a good operational efficiency is necessary a concise and efficient maintenance plan. Among the maintenance applied to the subsea robot are corrective, preventive and predictive maintenance. Therefore, the general objective of this work is to analyze the main operational failures presented by the vehicle and propose the application of MCC - Reliability Centered Maintenance, to indicate the critical failures and optimize the maintenance performed on the equipment, reducing costs, labor and increasing the availability of the same. For this, a bibliographic survey on the subject and documentary analysis was carried out to identify the technical data. The pareto diagram tool was applied to prioritize the recurrent failures, after that, the root causes were raised, with the application of the analysis of effects and failure modes and the fault tree and, finally, a reliability study of the equipment used in the vehicle was carried out. With the results analyzed, it was proposed the use of MCC by the company in its maintenance plan. DOI:https://doi.org/10.56238/uniknowindevolp-116